DELAYED ONSET NEUROPATHY ALONG WITH LARYNGEAL PARALYSIS -POLYNEUROPATHY COMPLEX DUE TO ORGANOPHOSPHATE POISONING - NEUROLOGICAL CASE REPORT IN A DOG - P.K. Ramkumar; M. Saravanan; R. Lakshmi; K. Karthika; D.T. Kaarthick; G. Manoj kumar (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Organophosphates (OP) and carbamates are widely utilized insecticides, but they also pose significant risks as sources ofintoxicationfor both humans and animals. A male non-descript dog, seven years old was presented with a chronic respiratory distress, dysphonia, exercise intolerance, and neurologic signs to Veterinary Clinical Complex, VCRI, Orathanadu on April 2023. Physical examination revealed elevated rectal temperature and congested mucous membrane with elevated heart beat and respiratory rate. Thoracic auscultation revealed muffled heart sound. The dog’s medical history indicated a potential case of organophosphate poisoning. Treatment involved administering atropine sulfate, normal saline, ceftriaxone, and furosemide. However, throughout the treatment process, the dog continued to experience upper respiratory stridor and dyspnoea. Clinical examination and radiographic observations confirmed the diagnosis of laryngeal paralysis. This case highlights the occurrence of laryngeal paralysis polyneuropathy complex in a canine affected by organophosphate poisoning.